1982
DOI: 10.1084/jem.155.6.1766
|View full text |Cite
|
Sign up to set email alerts
|

Helper T cells for cytotoxic T lymphocytes need not be I region restricted

Abstract: The development of procedures for the physical or functional separation of B cells and helper T cells permitted extensive studies to be performed that have elucidated the nature of cell-cell interactions that occur during the antibody response. Current models of B cell activation state that antigen-specific helper T cells are activated by recognition of antigen in the context of H-2 I region-encoded determinants on specialized antigen-presenting cells (APC) 1 and then deliver inducing signals to antigen-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Mice homozygous for the gld or the lpr mutation develop progressive lymphadenopathy and systemic autoimmune disease. In the C57BL/6 genetic background, these symptoms develop with significantly slower kinetics and decreased severity than in the autoimmuneprone MRL-lpr mice, which, in addition, suffer from arthritis and glomerulonephritis [43]. It is, therefore, remarkable that in the case of PKO-gld mice, the disruption of perforin and Fas ligand leads to severe lymphoproliferation and rapid lethality even in the relatively resistant C57BL/6 genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Mice homozygous for the gld or the lpr mutation develop progressive lymphadenopathy and systemic autoimmune disease. In the C57BL/6 genetic background, these symptoms develop with significantly slower kinetics and decreased severity than in the autoimmuneprone MRL-lpr mice, which, in addition, suffer from arthritis and glomerulonephritis [43]. It is, therefore, remarkable that in the case of PKO-gld mice, the disruption of perforin and Fas ligand leads to severe lymphoproliferation and rapid lethality even in the relatively resistant C57BL/6 genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this reservation, the notion we currently favor is that the K/D-restricted, effector T-cells for GVHD either do not require help or can produce their own endogenous help. On this point, it has recently been shown that certain K/D-restricted CTL can function in the absence of exogenous IL-2 (T-cell growth factor) {von , Widmer & Bach 1981, Raulet & Bevan 1982. Some of these cells produce IL-2-Iike factors.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, both helper and cytotoxicT cells are involved in the rejection of allogeneic skin grafts (reviewed in [lo]). It has been demonstrated previously that third-party MHC disparities serve as inducer determinants, allowing the generation of sufficient help to activate CTL precursors (CTLp) [lo, 111, and that T cell help is required for the generation of CTL [12][13][14].…”
Section: Discussionmentioning
confidence: 99%